# |
ODE |
Mathematica |
Maple |
\[
{}-\frac {\sin \left (\frac {x}{y}\right )}{y}+\frac {x \sin \left (\frac {x}{y}\right ) y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}1+y+\left (1-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{3}+y \cos \left (x \right )+\left (3 x^{2} y^{2}+\sin \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y}{1-x^{2} y^{2}}+\frac {x y^{\prime }}{1-x^{2} y^{2}} = 1
\] |
✓ |
✓ |
|
\[
{}2 y^{4} x +\sin \left (y\right )+\left (4 x^{2} y^{3}+x \cos \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime }+y}{1-x^{2} y^{2}}+x = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (1+\sqrt {x^{2}-y}\right ) = \sqrt {x^{2}-y}\, y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x \ln \left (y\right )+x y+\left (y \ln \left (x \right )+x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y^{2}}-\csc \left (y\right ) \csc \left (x \right )^{2}+\left (2 x y \,{\mathrm e}^{y^{2}}-\csc \left (y\right ) \cot \left (y\right ) \cot \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y^{2} \sin \left (2 x \right )-2 y \cos \left (x \right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x}{\left (x^{2}+y^{2}\right )^{{3}/{2}}}+\frac {y y^{\prime }}{\left (x^{2}+y^{2}\right )^{{3}/{2}}} = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} \left (1+\ln \left (y\right )\right )+\left (\frac {x^{3}}{y}-2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {-x y^{\prime }+y}{\left (x +y\right )^{2}}+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}\frac {4 y^{2}-2 x^{2}}{4 x y^{2}-x^{3}}+\frac {\left (8 y^{2}-x^{2}\right ) y^{\prime }}{4 y^{3}-x^{2} y} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-2 y^{2}+x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-3 x y-2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 3 \left (x^{2}+y^{2}\right ) \arctan \left (\frac {y}{x}\right )+x y
\] |
✓ |
✓ |
|
\[
{}x \sin \left (\frac {y}{x}\right ) y^{\prime } = y \sin \left (\frac {y}{x}\right )+x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+2 x \,{\mathrm e}^{-\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}x -y-\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x -6 y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 2 x y+y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{3}+y^{3}-y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y+4}{x -y-6}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y+4}{x +y-6}
\] |
✓ |
✓ |
|
\[
{}2 x -2 y+\left (y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y-1}{x +4 y+2}
\] |
✓ |
✓ |
|
\[
{}2 x +3 y-1-4 \left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1-x y^{2}}{2 x^{2} y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2+3 x y^{2}}{4 x^{2} y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y-x y^{2}}{x +x^{2} y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (\frac {y}{x}\right )-\cos \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{\frac {x}{y}}-\frac {y y^{\prime }}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}-x y}{y^{2} \cos \left (\frac {x}{y}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \tan \left (\frac {y}{x}\right )}{x}
\] |
✓ |
✓ |
|
\[
{}\left (3 x^{2}-y^{2}\right ) y^{\prime }-2 x y = 0
\] |
✓ |
✓ |
|
\[
{}x y-1+\left (x^{2}-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y+3 x^{3} y^{4} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+\left ({\mathrm e}^{x} \cot \left (y\right )+2 y \csc \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +2\right ) \sin \left (y\right )+x \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (x -2 x^{2} y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +3 y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (2 x -y \,{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \ln \left (y\right )-2 x y+\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+x y+1+\left (x^{2}+x y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+x y^{3}+3 y^{\prime } y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{x}+\frac {x^{3}}{y}+x \tan \left (\frac {y}{x^{2}}\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y = x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}\sec \left (x \right ) y^{\prime } = \sec \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}+y^{2}}{x^{2}-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +2 y}{2 x -y}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}-\sin \left (x \right ) \sin \left (y\right )+\cos \left (x \right ) \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = 2 x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-2 y = 3 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{2} = x
\] |
✓ |
✓ |
|
\[
{}\csc \left (x \right ) y^{\prime } = \csc \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y}{x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y^{2}+x^{2}}{x^{2}-2 y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x \cos \left (y\right )-x^{2} \sin \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {1}{y}-\frac {x y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{x} = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x -y
\] |
✓ |
✓ |
|
\[
{}L i^{\prime }+R i = E_{0} \operatorname {Heaviside}\left (t \right )
\] |
✓ |
✓ |
|
\[
{}L i^{\prime }+R i = E_{0} \delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}L i^{\prime }+R i = E_{0} \sin \left (\omega t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y+x \,{\mathrm e}^{y}
\] |
✗ |
✗ |
|
\[
{}y^{\prime }-y = 1
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+6 y = {\mathrm e}^{4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 2 \cos \left (5 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{-3 t} \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = {\mathrm e}^{-4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 1+t \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \left \{\begin {array}{cc} 0 & 0\le t <1 \\ 5 & 1\le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \left \{\begin {array}{cc} 1 & 0\le t <1 \\ -1 & 1\le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \left \{\begin {array}{cc} t & 0\le t <1 \\ 0 & 1\le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = t \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = t \,{\mathrm e}^{t} \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 y = \delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \delta \left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-\left (3 y+2 x \right ) y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-5 x y y^{\prime }+6 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+x y^{\prime }-y^{2}-y = 0
\] |
✓ |
✓ |
|